Spatial modeling of dengue and socio-environmental indicators in the city of Rio de Janeiro, Brazil Modelagem espacial da dengue e variáveis socioambientais no Município do Rio de Janeiro, Brasil - Tatiana Rodrigues de Araujo Teixeira; Oswaldo Gonçalves Cruz (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This study analyzed the spatial distribution of dengue in Rio de Janeiro, Brazil, in 2006, and associations between the incidence per 100,000 inhabitants and socio-environmental variables. The study analyzed reported dengue cases among the city's inhabitants, rainfall, Breteau index (for Aedes aegypti and Aedes albopictus), Gini index, and social development index. We conducted mapping and used the global Moran index to measure the indicators' spatial autocorrelation, which was positive for all variables. The generalized linear model showed a direct association between dengue incidence and rainfall, one-month rainfall time lag, Gini index, and Breteau index for A. albopictus. The conditional autoregressive model (CAR) showed a direct association with rainfall for four months of the year, rain time lag in July, and Gini index in February. The results demonstrate the importance of socio-environmental variables in the dynamics of dengue transmission and the relevance for the development of dengue control strategies. Analisaram-se a distribuição espacial da dengue na cidade do Rio de Janeiro, Brasil, em 2006, e associações entre sua incidência por 100 mil habitantes e variáveis socioambientais. Consideraram-se os casos notificados de residentes no município, o índice pluviométrico, o índice de Breteau (para Aedes aegypti e Aedes albopictus), o índice de Gini e o índice de desenvolvimento social. Realizou-se o mapeamento e mensurou-se a autocorrelação espacial dos indicadores pelo índice global de Moran, sendo essa positiva para todas as variáveis. O modelo linear generalizado evidenciou associação direta entre a incidência e chuva; time-lag de um mês para chuva; índice de Gini e índice de Breteau para Aedes albopictus. Através do modelo espacial CAR (conditional autoregressive), encontrou-se associação direta com chuva em quatro meses do ano; time-lag de chuva em julho e índice de Gini em fevereiro. Esses resultados evidenciam a importância de variáveis socioambientais na dinâmica de transmissão da dengue, e sua relevância como subsídios às estratégias de controle.